Quantitative Proteomics Analysis of ABA- and GA3-Treated Malbec Berries Reveals Insights into H2O2 Scavenging and Anthocyanin Dynamics - Murcia, Mauro Germán (2024)
Abscisic acid (ABA) and gibberellic acid (GA3) are regulators of fruit color and sugar levels, and the application of these hormones is a common practice in commercial vineyards dedicated to the production of table grapes. However, the effects of exogenous ABA and GA3 on wine cultivars remain unclear. We investigated the impact of ABA and GA3 application on Malbec grapevine berries across three developmental stages. We found similar patterns of berry total anthocyanin accumulation induced by both treatments, closely associated with berry H2O2 levels. Quantitative proteomics from berry skins revealed that ABA and GA3 positively modulated antioxidant defense proteins, mitigating H2O2. Consequently, proteins involved in phenylpropanoid biosynthesis were downregulated, leading to decreased anthocyanin content at the almost ripe stage, particularly petunidin-3-G and peonidin-3-G. Additionally, we noted increased levels of the non-anthocyanins Eviniferin and quercetin in the treated berries, which may enhance H2O2 scavenging at the almost ripe stage. Using a linear mixed-effects model, we found statistical significance for fixed effects including the berry H2O2 and sugar contents, demonstrating their roles in anthocyanin accumulation. In conclusion, our findings suggest a common molecular mechanism by which ABA and GA3 influence berry H2O2 content, ultimately impacting anthocyanin dynamics during ripening.